Effectiveness of siwak salvadora persica extract to aggregatibacter actinomycetemcomitans as one of pathogenic bacteria causing periodontal disease - Arni I. Djais; Vidya Y. Tope (DiscoverSys Inc., 2017)
Objective : Periodontal disease is one of oral and dental diseases which most commonly found in humans caused by several factors, one of them due to the accumulation of bacterial plaque. Aggregatibacter actinomycetemcomitans is a bacterial pathogen that frequently causes periodontal disease.Material and Methods : To inhibit the growth of these bacteria can be done by using natural ingredients that contain anti-bacterial agent. One of the natural ingredients that contain antibacterial substances is Siwak. To determine the effect of siwak extract against bacteria Aggregatibacter actinobaciluscomnitans as one of the pathogenic bacteria causing periodontal diseases. The study was laboratory experimental with posttest only control group design.Results : This study used sample of Aggregatibacter actinomycetemcomitans colonies in MHA medium. Twenty four samples were divided into six treatment groups, they were 5 groups given the extract siwak with concentration of 3.125%, 6:25%, 12.5%, 25%, 50% and 1 group treated with control DMSO 5%. Inhibition zone was measured after 48 hours incubation at 37Â°C and measured using caliper. Data analysis was performed using Kruskal Wallis test. The mean diameter of inhibition zone at concentrations of 3.125%, 6:25%, 12.5%, 25%, and 50% were 6.4 mm, 7.0 mm, 7.2 mm, 7.9 mm and 8.6 mm.Conclusion : Siwak extract can inhibit the growth of Aggregatibacter actinomycetemcomitans as one of the pathogenic bacteria causing periodontal diseases with the largest concentration is a concentration of 50% and the smallest concentration that is 3.125%.